2019
DOI: 10.7596/taksad.v8i2.2153
|View full text |Cite
|
Sign up to set email alerts
|

Female Entrepreneurship: Types of Economic Activity

Abstract: In recent years women entrepreneurs have made a significant contribution to the economic growth of most countries. Therefore, at the present stage of the entrepreneurship study, it is relevant to analyze the patterns that characterize the current level of women's entrepreneurial activity as well as determine the sectoral structure of women's entrepreneurship. The purpose of the study is a comprehensive assessment of women's early entrepreneurial activity and their sectoral preferences in creating their own bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…When developing the residue distribution function, the methodology given in the articles (Pinkovetskaia et al, 2019;Pinkovetskaia et al, 2020) (3)…”
Section: Results Presented In Tablementioning
confidence: 99%
“…When developing the residue distribution function, the methodology given in the articles (Pinkovetskaia et al, 2019;Pinkovetskaia et al, 2020) (3)…”
Section: Results Presented In Tablementioning
confidence: 99%
“…According to recent statistical data, the female activities in entrepreneurship are based on the TEA ranking for the entrepreneurship activities. Pinkovetskaia et al, 2019) In the gulf countries, women have been restricted to join their potential hand in the economic development. Taking into consideration of Islamic tradition, they believe that women are not physically strong to perform any kind of hard activities and also they are not able to handle the tough situation.…”
Section: Theme 2: Activities Of Female Entrepreneurship In the Develomentioning
confidence: 99%
“…Taking into consideration of Islamic tradition, they believe that women are not physically strong to perform any kind of hard activities and also they are not able to handle the tough situation. As opined by Pinkovetskaia et al, (2019), in the ancient time most of the women are only perform their activities in the agricultural sectors and engage themselves for the family welfare. As per the statistical data of Central Department of Statistics and Information in the year 2013, Saudi women above 15 years are unemployed as compared to 6.1% men in the kingdom of Saudi Arabia.…”
Section: Theme 2: Activities Of Female Entrepreneurship In the Develomentioning
confidence: 99%
See 1 more Smart Citation
“…This is despite the fact they face more serious challenges in their activities when compared to male entrepreneurs. Research in gender studies has demonstrated that women generally still face significant obstacles to entrepreneurship (Vossenberg, 2013) in the areas of reduced human capital, limited strategic choice options, and institutionalised structural barriers including taxation and legal disparities in the governance of industry in most countries (Pinkovetskaia, Kryukova, Campillo, & Rojas-Bahamon, 2019;Širec & Močnik, 2012). In addition, the socially constructed genres of 'male' and 'female' are gendered with inherent political, social, economic, and structural inequities that these signifiers entail.…”
Section: Introductionmentioning
confidence: 99%